Pré-tratamento por explosão a vapor em resíduos de pele bovina para extração de gelatina visando aplicação como filmes e revestimentos - Rigueto, Cesar Vinicius Toniciolli (2024)
This thesis aimed to extract gelatin from bovine hides using the steam explosion as pretreatment and its application as films and coatings. The steam explosion was applied at 110, 120, and 130 °C for 1, 5, and 10 minutes. The gelatins were extracted in water at 65 °C and characterized for dry matter, ash, pH, conductivity, viscosity, and protein content using the Lowry and NTK methods. The samples with the highest protein content and viscosity, as well as the sample obtained under the mildest pre-treatment condition, were further characterized by FTIR, thermogravimetry, amino acid profile, and molecular weight (Mw). Subsequently, they were purified using ultrafiltration membranes, with and without enzymatic treatment using 2.5% (w/w) transglutaminase (TGase). The purified, lyophilized, and cross-linked gelatins with TGase were used to develop polymeric films with and without the addition of thyme essential oil (TEO) and characterized for thickness, tensile strength, elongation, water solubility, water vapor permeability, color parameters, FTIR, and thermogravimetry. The antimicrobial potential of TEO was evaluated using disc diffusion, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) tests. The gelatin and TEO film-forming solutions were applied as coatings on chicken fillets, stored for fifteen days, and evaluated for weight loss, pH, mesophilic aerobic microorganism count, and Enterobacteriaceae count at fiveday intervals. For the gelatin extraction, both temperature and time were significant (p<0.01) for all studied variables. Samples extracted at 120ºC/10min and 130ºC/10min had higher protein content (24.83 and 28.26 g/L), viscosity (7.92 and 11.06 cP), total amino acids (74.39 and 72.15 g/100g), and lower ash content (8.69 and 8.60%) and pH (10.58 and 10.33). Mw increased with higher time and temperature (30–69 kDa). Ultrafiltration purification reduced ash content by 61% to 90%, reaching approx. 2% after two diafiltrations. Enzymatically treated and purified gelatins had higher Mw (31–69 kDa) compared to those without treatment (6.10–14.08 kDa). In polymeric film production, gelatin extracted after pretreatment at 130 ºC for 10min showed greater tensile strength and lower solubility (7.23 MPa and 76.45%) compared to pretreatment at 120 ºC for 10min (2.72 MPa and 87.56%). The addition of TEO affected the properties of the films depending on the type of gelatin used. Chicken fillets coated with gelatin and TEO had significantly lower weight loss and pH (p<0.05) compared to uncoated samples, though there was no significant reduction (p>0.05) in Enterobacteriaceae and mesophilic aerobic microorganism counts. Overall, steam explosion reduced processing time and preserving protein integrity. Additionally, the extracted and purified gelatin demonstrated viable applications, standing out as a raw material for the development of polymeric films and coatings.